SSR marker based profiling and population structure analysis in peach (Prunus persica) germplasm - RAJENDER KUMAR; D C DIMRI; KANCHAN KARKI; K M RAI; N K SINGH; JITENDRA SINGH SHIVRAN; SWAPNIL BHARTI (The Indian Journal of Agricultural Sciences, 2023)
For breeding programmes to be successful and for germplasm conservation, it is essential to characterize and analyze the genetic diversity of available germplasm. The present experiment was conducted at Molecular Biology and Genetic Engineering Laboratory of Uttarakhand Council for Biotechnology, Haldi, Uttarakhand during 2022 to study the molecular profile of 41 peach [Prunus persica (L.) Stokes] accessions using 23 polymorphic SSR markers. The number of alleles detected ranged from 3 to 8 with an average of 4.65 alleles per locus (Na) and a total of 107 alleles were amplified. The average effective number of alleles (Ne) were 2.89 per marker. The SSR marker MA015a produced maximum number of 8 alleles followed by BPPCT 015 and CPPCT14 which produced 7 alleles each. The polymorphic information content (PIC) varied between 0.317–0.836 with a mean value of 0.563. The observed heterozygosity examined was lower (Ho = 0.02) and the expected heterozygosity (He = 0.61) ranged between 0.34 to 0.85. The presence of a higher Shannon’s information index (I) of 1.17 indicates higher diversity in the given set of peach genotypes. Jaccard’s similarity coefficient ranging from 0.533 to 1, indicated a pair-wise relationship among the peach accessions. The cluster dendrogram partitioned the accessions into two main clusters. However, the total accessions were stratified into 3 groups (K=3) based on population structure analysis which was further confirmed by Principal Coordinate Analysis (PCoA). The information generated in the study may have great implications in molecular characterization, fingerprinting and documentation of accessions in the peach improvement programme.